Entrepreneurship Education and Creation of Postgraduate Entrepreneurs in a Post-Socialist Economy - Allan, Issack Shimba (Papers in Education and Development, 2021)
This article presents empirical findings of a study conducted in three Tanzanian universities. The study arose from observations that most of the students taking MBA evening classes pursue their studies while already employed in various organisations, a situation which spurs debates about the value of entrepreneurship education in their career. Both quantitative and qualitative data was collected involving 442 students. Findings show that generally, over 80% of the students have a positive perception about the relevance of entrepreneurship education. However, a few of them don ' t appreciate it for various reasons, including the need to focus its contents more on intrapreneurship than entrepreneurship. The article contributes to teaching practices and policies on making entrepreneurship education more impactful. Keywords: entrepreneurship, entrepreneurship training, learning styles, postgraduate students, Tanzania